Cross-national Differences in Computer-Use Ethics: A Nine-country Study - Whitman, Michael E.; Townsend, Anthony M.; Hendrickson, Anthony R. (Journal of International Business Studies, 1999)
This study examines computer-use ethics among nine countries (Singapore, Hong Kong, United States, Great Britain, Australia, Sweden, Wales, and the Netherlands). Based on Paradice [1990], an instrument was developed containing three scales focusing on ethical attitudes toward software license infringement, use of virus programs, and misuse of corporate computing resources. Analysis indicates that there are significant differences in ethical values among nationalities for each of these scales.